2001
DOI: 10.1007/s004170100270
|View full text |Cite
|
Sign up to set email alerts
|

Surgery for nystagmus related head turn: Kestenbaum procedure and artificial divergence

Abstract: Artificial divergence is preferable or should be combined with Kestenbaum surgery, if possible. Kestenbaum surgery alone has an effect/dose ratio similar to recess-resect surgery for strabismus. Thus, to correct x degrees HT, 2/3x mm surgery on each eye is adequate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 18 publications
1
13
0
2
Order By: Relevance
“…6 Surgery is usually not done prior to 6 years because a spontaneous decrease in head turn is possible. 7,8 This was corroborated by many of our patients who reported that initially the face turn was larger and gradually has improved to the present level. There is also possible variability in the face turn.…”
Section: Discussionsupporting
confidence: 80%
“…6 Surgery is usually not done prior to 6 years because a spontaneous decrease in head turn is possible. 7,8 This was corroborated by many of our patients who reported that initially the face turn was larger and gradually has improved to the present level. There is also possible variability in the face turn.…”
Section: Discussionsupporting
confidence: 80%
“…Thus, after compensation of the cyclodeviation, the surgery on the oblique muscles has an additional positive effect on the head posture and increases the Kestenbaum effect. This might explain why good reduction of the head posture was reached with less surgery than reported in previous studies given on vertical and horizontal procedures [4,5,17]. So simultaneous procedures on the oblique muscles not only compensate for cyclodeviation, but the intended effect on head posture is also increased so that dosage of surgery on the vertical recti might be kept relatively low to prevent adverse side-effects.…”
Section: Discussionmentioning
confidence: 86%
“…Because of the high rates of recurrence and undercorrection, the dosages suggested by Parks were augmented by either 40% for patients with head turn of 30°, resulting in surgery of 7 mm, 8.4 mm, 9.8 mm, and 11.2 mm on the rectus muscles, or 60% for patients with head turn of 45°, which results in surgery of 8 mm, 9.6 mm, 11.2 mm and 12.8 mm. Recently, larger studies, for example by Gräf et al [4,5] confirmed the need for higher dosages for the correction of an abnormal horizontal head posture. Gräf et al concluded that surgery in mm on each eye should be two-thirds of the horizontal head turn in degrees, i.e.…”
Section: Discussionmentioning
confidence: 97%
“…The dosage of ocular muscle retroposition/resection depends on the angle of AHP with fixation of distant target. The reduction of abnormal head turn with 1mm muscle resection was 1.4˚ head turn on average in one study (Gräf et al, 2001). …”
Section: Clinical Significance Of Head Posture Measurementmentioning
confidence: 85%